If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4+3)(2-5)=y-15
We simplify the equation to the form, which is simple to understand
(4+3)*(2-5)=y-15
Reorder the terms in parentheses
multiplication of parentheses
(-21)=y-15
Remove unnecessary parentheses
-21=y-15
We move all terms containing y to the left and all other terms to the right.
-1y=-15+21
We simplify left and right side of the equation.
-1y=+6
We divide both sides of the equation by -01 to get y.
y=-6
| 5x+5=-27-2x | | -34*26+x=18 | | x+0=x-0 | | 8x+2(x-8)=10x-16 | | (n+5)*(n-5)=12 | | h^4+12=7h^2 | | 8ab^2-12ab=0 | | 13-x=9-x | | w-1/4u=0 | | 3x^(2/5)-5=22 | | (10-x)-3=1 | | 4a+4c=52 | | -112/22 | | 4r+8=8-16r | | 6=-3x+59 | | 7+3x+8= | | 4x^2-31x+18=-8x+3 | | W-1/4u | | (8x+5)=(3x+10) | | 4p+5q=14 | | 4.2x=12.25 | | rts=qk | | 16x^2-80x-100-(9x^2+6x+1)=0 | | (7/11)^2 | | 3x+26=7(x-6) | | 144/3=76 | | y=-9x+12 | | 4/5x=x-32 | | 5-2x=6x-3 | | 2/3x0=5 | | 4(4x^2-20x+25)-(9x^2+6x+1)=0 | | x*10+30=x*6+126 |